Legal Aspects of Failure to Pay Online Loans in Indonesia in The Use of Financial Technology - Reyna Zahia; Surahmad Surahmad (Green Publisher Indonesia, 2024)
Financial Technology (Fintech) is a financial service that uses a technology base that makes it easier for transactions to be carried out anywhere and at any time. Currently, one of the services in Indonesia is Financial Technology or Fintech which is developing rapidly, especially online loans because it has been proven that many people are interested. The existence of online loans or peer to peer lending as a form of financial technology (Fintech) is the impact of technological advances which offer many loans with easier and more flexible terms and conditions compared to conventional financial institutions such as banks. This development must be accompanied by good legal instruments to avoid existing risks. The research method used is normative research with a statutory approach. The results of this research refer to several articles. Namely. Article 1320 of the Civil Code, so that an agreement arises from an agreement. Then, Financial Services Authority Regulation Number POJK No. 10/POJK.05/2022 as well as other regulations to improve consumer protection. Regarding Information Technology-Based Money Lending and Borrowing, Law Number 8 of 1999 concerning Consumer Protection.